(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Gluten consumption in genetically predisposed individuals causes celiac disease (CD), a chronic immune-mediated enteropathy of the small intestine. 1 It is an autoimmune condition,It is not an allergy or sensitivity, which distinguishes it from gluten intolerance. According to international surveys, the worldwide prevalence of celiac disease is 1.4%. 2 Although the gastrointestinal symptoms of CD, including diarrhoea, stomach pain, bloating, and vomiting, are well-known, many patients also experience extraintestinal symptoms, such as arthritis and dermatitis herpetiformis. Aim’s &Objectives: Celiac disease is a prevalent multisystemic autoimmune illness. It is now widely acknowledged that the disease may appear with extraintestinal signs, which complicate its diagnosis. The purpose of this study was to evaluate the extraintestinal ENT manifestations of celiac disease, as well as its pathophysiology and therapy, in order to demonstrate that some patients with celiac disease may initially present to an otolaryngologist. Increasing understanding of celiac disease otolaryngologists may assist in the accurate diagnosis and therapy approach. Methods & Materials: A literature review was undertaken utilising the PubMed database to discover original publications published between 2000 and 2020 regarding celiac disease and ENT symptoms. coeliac disease AND ENT manifestations OR hearing loss OR epistaxis OR nasal septal perforation OR obstructive sleep apnoea OR vertigo OR tonsillitis OR sinusitis) Only English-language articles were reviewed. In total, 17 papers satisfied the inclusion criteria. Sensorineural hearing loss, obstructive sleep apnea, nasal septal perforation, epistaxis, and vertigo with nystagmus are extraintestinal ENT signs of celiac disease. Results: It is believed that immunologically mediated pathways cause sensorineural hearing loss, obstructive sleep apnea, nasal septal perforation, vertigo, and nystagmus, whereas intestinal malabsorption causes epistaxis. Conclusions: Celiac disease can generate extraintestinal ENT signs, which necessitates a high index of suspicion from the otolaryngologist in order to identify and manage appropriately. A gluten-free diet may provide adequate symptom relief for the majority of symptoms. Celiac disease-related sensorineural hearing loss appears gradual and permanent and may require periodic audiological monitoring.